Reconstructive Strategies in Pediatric Patients after Oncological Chest Wall Resection: A Systematic Review - Lonnee, Pieter W.; Ovadja, Zachri N.; Hulsker, Caroline C.C.; van de Sande, Michiel A.J.; van de Ven, Cornelis P.; Paes, Emma C. (European Journal of Pediatric Surgery, 2023)
An appropriate reconstruction strategy after surgical resection of chest wall tumors in children is important to optimize outcomes, but there is no consensus on the ideal approach. The aim of this study was to provide an up-to-date systematic review of the literature for different reconstruction strategies for chest wall defects in patients less than 18 years old. A systematic literature search of the complete available literature was performed and results were analyzed. A total of 22 articles were included in the analysis, which described a total of 130 chest wall reconstructions. All were retrospective analyses, including eight case reports. Reconstructive options were divided into primary closure (n = 21 [16.2%]), use of nonautologous materials (n = 83 [63.8%]), autologous tissue repair (n = 2 [1.5%]), or a combination of the latter two (n = 24 [18.5%]). Quality of evidence was poor, and the results mostly heterogeneous. Reconstruction of chest wall defects can be divided into four major categories, with each category including its own advantages and disadvantages. There is a need for higher quality evidence and guidelines, to be able to report uniformly on treatment outcomes and assess the appropriate reconstruction strategy.
Keywords: chest wall reconstructions; chest wall tumors; reconstructive surgery; pediatric surgery